Collective commitment - Christian Roessler; Sandro Shelegia; Bruno Strulovici (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2015)
We consider collective decisions made by agents whose preferences and power depend on past events and decisions. Faced with an ineffcient equilibrium and an opportunity to commit to a policy, can the agents reach an agreement on such a policy? Under an intuitive condition linking power structures in the dynamic setting and at the commitment stage, the answer is negative: when the condition holds, the only agreement that may be reached at the outset, if any, coincides with the equilibrium without commitment. The condition is also necessary: when it fails, as in the case of a single time-inconsistent agent, commitment is valuable for some payoffs. We apply our result to explain inefficient collective decisions in the contexts of investment in a public good, hiring, and reform.
Keywords: D70; H41; C70; 330